PARTISIPASI GAPOKTAN MULYO ASRI DI DESA JENGGRIK KABUPATEN NGAWI UNTUK PENGENDALIAN HAMA DAN PENYAKIT KEDELAI BERBAHAN KULIT BIJI JAMBU METE - Wuye Ria Andayanie; Indah Rekyani Puspitawati; Ratna Mustika Wardhani (Jurnal Terapan Abdimas, 2025)
Abstract. Participation comunication for soybean farmers is carried out to reduce the use of chemical pesticides is absolutely necessary in sustainable and environmentally friendly agricultural activities. Farmer extension in community-based service activities aims to determine the level of farmer participation in the implementation of pest and disease control programs on cashew nut shell plants. The method of implementing community-based service uses purposive sampling. Samples were taken from 28 respondents from the Gapoktan "Mulyo Asri". Data collection techniques through direct interviews with farmers based on a list of questions and direct observation of respondents carried out interactively and documentation. The level of farmer participation was measured by inferential statistics using the multivariate analysis method. Evaluation results of the distribution of participation levels in the use of insecticides and antivirals made from cashew nut shells is in the low category with an average percentage of 32.58%. However, after community service activities, there was an increase in farmers' understanding and skills in utilizing cashew nut shell waste as an insecticide and antiviral in controlling pests and diseases in soybean plants. The results of the unpaired t-test for chemical pesticide users were 47.48 ± 7.21. The value can be said to be in the normal category. Meanwhile, the farmer group using herbal pesticides made from cashew nut skins has an average value of 45.13 ± 4.72. This value has a range close to the use of chemical pesticides.   Abstrak. Partisipasi pada petani kedelai dilakukan untuk mengurangi penggunaan pestisida kimia mutlak sangat diperlukan dalam kegiatan pertanian yang berkelanjutan dan berwawasan lingkungan. Kegiatan pengabdian berbasis masyarakat bertujuan untuk mengetahui tingkat partisipasi petani dalam pelaksanaan program pengendalian hama dan penyakit pada tanaman berbahan kulit biji jambu mete.  Metode pelaksanaan pengabdian berbasis masyarakat menggunakan purposive sampling. Sampel diambil dari 28 responden dari Gapoktan Mulyo Asri. Teknik pengumpulan data melalui wawancara langsung ke petani berdasarkan daftar pertanyaan dan observasi langsung ke responden yang dilakukan secara interaktif serta dokumentasi. Tingkat partisipasi petani diukur dengan statistik inferensia menggunakan metode analisis multivariate. Hasil evaluasi dari distribusi tingkat partisipasi petani kedelai terhadap kegiatan penggunaan insektisida dan antiviral berbahan kulit biji jambu mete dalam kategori rendah dengan rata-rata persentase 30,84 %.  Namun demikian setelah kegiatan pengabdian berbasis masyarakat terjadi peningkatkan pemahaman dan keterampilan petani dalam pemanfaatan bahan limbah kulit biji jambu mete sebagai insektisida dan antiviral dalam pengendalian hama dan penyakit pada tanaman kedelai.  Hasil uji unpaired t-test pengguna pestisida kimia adalah 47,48 ± 7,21. Nilai tersebut dapat dikatakan pada kategori normal. Sedangkan kelompok tani pengguna pestisida nabati berbahan kulit biji jambu mete mempunyai nilai rata-rata 45,13 ± 4,72. Nilai ini mempunyai rentang mendekati penggunaan pestisida kimia.